An empirical study of information technology infrastructure capability and its impact on digitally enabled customer management processes in life insurance companies. (1st January 2013) - Mani, R.V.S.; Baul, Utpal; Mohanty, R.P.; Rajkumar, T.M.
Academic marketing literatures have increasingly studied about customer management processes. However, there is limited investigation to understand the integration of information technology infrastructure to leverage customer management processes for performance gains. This paper provides an approach to address the impact of each of the individual information technology capabilities on customer management processes. It also provides an empirical analysis of the impact on intermediate business process outcome. The research model proposed is unique in its nature and attempted for the first time, where the academicians and the practitioners can gain insight into the impact of each individual information technology infrastructure capabilities on digitally enabled customer management business processes. This paper uses objective measurement for the process outcome relevant to the industry and customer management business processes. This approach is generic enough to apply for analysing impact of information technology capabilities on business processes specific to an industry.